2015
DOI: 10.1016/j.memsci.2014.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Understanding particle deposition kinetics on NF membranes: A focus on micro-beads and membrane interactions at different environmental conditions

Abstract: The significance of nanofiltration membrane surface properties when interacting with microbeads with and without permeate flux was investigated. This was achieved by characterising the surface tension and zeta potential of micro beads and NF90 membranes to determine the colloid-membrane interaction forces. Dynamic adhesion assays under different ionic strengths (0.1M and 0.01M) and pH (5, 7, 9) were conducted. Experimental results showed that at high ionic strength, pH does not have a significant effect on adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 23 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…Interfacial Gibbs free energies at a minimum separation distance between membrane surface and microalgal cells were calculated based on the surface tension data from Table1 and are shown in Table 2. The contribution of EL free energy is normally a magnitude lower than that of LW and AB free energies and can be considered as negligible (Cao et al, 2015;Zhao et al, 2016a). The total interfacial Gibbs free energy ( 0 ) was therefore calculated by the sum of 0 and 0 .…”
Section: Characterization Of Membranes and Microalgaementioning
confidence: 99%
“…Interfacial Gibbs free energies at a minimum separation distance between membrane surface and microalgal cells were calculated based on the surface tension data from Table1 and are shown in Table 2. The contribution of EL free energy is normally a magnitude lower than that of LW and AB free energies and can be considered as negligible (Cao et al, 2015;Zhao et al, 2016a). The total interfacial Gibbs free energy ( 0 ) was therefore calculated by the sum of 0 and 0 .…”
Section: Characterization Of Membranes and Microalgaementioning
confidence: 99%
“…A recent study also reported that bacterial adhesion is influenced by more than electrostatic and hydrophobic interactions when there is a flux [45]. Model predictions indicated that the drag force overcome all other colloidsurface interaction forces when the flux increases to a certain level (7.2 L/h m 2 ) on NF membranes.…”
Section: Correlation Between Cell Surface Characteristicsmentioning
confidence: 90%
“…Interfacial Gibbs free energies were calculated based on the surface tension data (Table 2). The contribution of the EL free energy is normally a magnitude lower than that of LW and AB free energies and can be considered as negligible [54,62]. The total interfacial Gibbs free energy ( 0 ) was therefore calculated by the sum of 0 and 0 .…”
Section: Characterization Of Membranes and Microalgaementioning
confidence: 99%